Foreign assistance investments contribute to U.S. economic growth and employment - Board for International Food and Agricultural Development; International Food Policy Research Institute; Association of Public and Land-Grant Universities (International Food Policy Research Institute, 2019)
Foreign agricultural assistance supports growth in household incomes abroad, increasing demand for U.S. agricultural and manufactured exports with broad impacts on economic growth and employment. Research supported by U.S. foreign agricultural assistance has produced new wheat technologies now widely adopted by American farmers. Many American producers of sorghum now plant improved varieties developed through a sorghum research program sponsored by USAID. USAID-sponsored research on beans generates innovations that benefit U.S. producers and consumers of beans.